Influence of Hard vs. Soft Ground Surfaces on Bone Accretion in Prepubertal Footballers - Carmona, M. Plaza-; Vicente-Rodriguez, G.; Martín-García, M.; Burillo, P.; Felipe, J. L.; Mata, E.; Casajús, J. A.; Gallardo, L.; Ara, I. (International Journal of Sports Medicine, 2014)
Information regarding osteogenic effects of physical activity performed on different playing surfaces is scarce. A total of 42 children (9.2±0.2 years, Tanner stages I–II) participated in this study. 14 were playing on artificial turf soft ground (SG), 14 on a natural non-grass hard ground (HG) and 14 were assigned to the sedentary control group (C). Whole body and hip scans (dual energy X-ray absorptiometry), anthropometric variables (weight and height) and physical fitness (VO2max) were determined in all participants. Bone mineral content (BMC) values were higher in the SG group compared to the C group at the legs (209.75±5.11 g vs. 187.42±5.14 g, respectively), pelvis (122.72±4.27 g vs. 98.58±4.29 g respectively) and whole-body level (1 126.1±22.81 g vs. 1 035.34±22.92 g, respectively). The hard ground (HG) group also showed higher values in the majority of BMC variables compared to the C group. Additionally, bone mineral density (BMD) was significantly higher at all sites of the hip in both active groups compared to control (P<0.05). No differences between HG and SG were found. In summary, similar bone mass accretion is obtained by prepubescent footballers independently of the surface on which they practice football.
Keywords: bone; development; physical activity; footballer; turf